Obstetric Consequences of Pregnant Females with COVID-19: A Systematic Review - Sabira Sultana; Rizwana Dilshad; Asia Hussain; Rabia Nisar; Saharish Khaliq; Kehekshan Shahzadi; Mehshaar Amina Mehboob; Naheed Akhtar; Muhammad Akram; Gull Naz; Aqsa Afzal (Kurdish Studies, 2024)
Since its discovery in December 2019, COVID-19 has spread to over 210 nations, with a mortality rate of three to four percent. Its consequences on a pregnant woman are mostly unknown. The systemic review's goal was to report on the obstetric outcomes of pregnant women who had Covid-19 until October 2020. To analyse some confirmed patients of parental, foetal, or neonatal death due to Covid-19 infection, data was searched from Scopus, PubMed, Web of Science database, and Google Scholar. Data on the effects of Covid-19 in pregnancy on parental, obstetric, and infant outcomes were included in the studies.The data gathered in this systematic review might aid healthcare personnel in providing the best possible therapy. The findings might help to guide and enhance prenatal therapy for women who are infected with Covid-19 during pregnancy.